2018
DOI: 10.1002/star.201800243
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Free and Biocompatible Hydrogel via Hydrazone Chemistry: Synthesis, Characterization, and Bioassessment

Abstract: Functionalization of starch with oxidative cleavage reaction to yield the corresponding dialdehyde derivatives has been employed as an approach for gel formation via Schiff's base reaction. However, this reaction is known as reversible and hydrolysable in aqueous solutions. In this study, the potential of hydrazone chemistry to be used in the synthesis of stimuli‐free and stable hydrogels is investigated. Soluble starch is selectively oxidized to give aldehydic‐starch with different aldehyde contents 39.9, 34.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Ethylene glycol was added at the end of the reaction to remove the excess amount of periodate. The obtained solution was dialyzed against distilled water several times to get rid of the excess sodium iodide and then freeze‐dried to obtain the DAH …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene glycol was added at the end of the reaction to remove the excess amount of periodate. The obtained solution was dialyzed against distilled water several times to get rid of the excess sodium iodide and then freeze‐dried to obtain the DAH …”
Section: Methodsmentioning
confidence: 99%
“…The aldehyde group content was determined using the rapid quantitative alkali consumption method . Dried oxidized substrate (0.2 g) was weighed into a 125‐mL Erlenmeyer flask, and 10 mL of standardized 0.2M sodium hydroxide was added.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, since the hydrogel possessed good flexibility, the authors showed the dependence of resistance on the angle of bending or change length under compression proving a potential application in soft sensors and biocompatible devices. It is worth pointing out, as a suggestion for future systems, that more stable hydrazone groups can be formed between hydrazine and aldehyde/ketone, while the hydrogel can be achieved faster compared to the hydrogels that are based on imine bonds [ 148 ].…”
Section: Preparation Of Electric Conductive Hydrogels Based On Natural Polymersmentioning
confidence: 99%
“…The IPNs are responsive not only for the chemical architecture of the macromolecular matrices, but also for the surrounding conditions such as pH, ionic strength, temperature, magnetic field, etc. These systems that are termed as intelligent polymers are nowadays in the focus of many researchers due to their biomedical applications such as artificial implants, drug‐delivery systems, dialysis membranes, etc 22‐29 …”
Section: Introductionmentioning
confidence: 99%